Tlingit canoe in front of government buildings, Sitka, Alaska, 1914 - Curtis, Asahel, 1874-1941
Carved and painted canoe pulled up onto grass beside cannons facing the waterfront, across the road in the background are several multistoried buildings flying the American flag; merchant tents are set up on the sidewalk in front of the buildings.